Perbaikan Postur Kerja melalui Konsep Tri Angga untuk Meningkatkan Kualitas Kesehatan Pendeta Hindu di Pura Tirta Empul Tampaksiring Bali - Ni Ketut Dewi Irwanti; Ida Ayu Sri Adnyani (Universitas Udayana, 2022)
This study aimed to improve the posture or body position of Hindu lay man priest while working using the three body elements known as Tri Angga concept to improve the health quality. The health quality improvement was measured from the decrease of workload, fatigue, and muscle complaints. This was a real experimental research using the same subject or treatment by subjects design. The population was those who meet the inclusion criteria. Saturated sampling technique was used for the sample. Data were collected before and after the posture improvement. The results showed a decrease in workload by 12%, general fatigue by 24.26% and muscle complaints by 28.80%. Rapid Upper Limb Assessment (RULA) analysis results showed that there was a score decrease from six to three. Further research is recommended to conduct more holistic ergonomic intervention in the prayer process by considering the local wisdom in order to create effective, comfortable, safe, healthy and efficient conditions (ENASE).